Dynamism of Minimum Age of Marriage in Muslim Countries: A Study of Marriage in Indonesia, Tunisia, and Turkey - Aziz, Abdul (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract The setting of the minimum age for marriage in various Muslim countries, including Indonesia, Tunisia, and Turkey, has variations based on Islamic law, madhhab fiqh, and local social and cultural considerations. Although there is no strict rule regarding the minimum age in Islamic law, many countries set age limits to protect individuals from early marriage which is often associated with health, psychological and domestic stability problems. This study uses a qualitative method with a comparative approach, examining various laws and marriage rules in the three countries, as well as the theory of Maqasid al-Shari'ah, which emphasizes the protection of offspring and family welfare. The findings of the study show that Indonesia has raised the minimum age of marriage to 19 years for both men and women, Tunisia applies 18 years old for both, while in Turkey, the minimum age is 17 years for women and 18 years for men. The main results of the discussion showed that these differences were influenced by differences in fiqh schools and national needs, such as divorce prevention and protection of children's rights. The study concludes that the minimum age for marriage in the three countries is part of an effort to maintain a balance between religious law and social reality. Keywords: Minimum Age Limit for Marriage, Muslim Countries, Islamic Marriage Law Abstrak Penetapan batas usia minimum untuk perkawinan di berbagai negara Muslim, termasuk Indonesia, Tunisia, dan Turki, memiliki variasi yang didasarkan pada hukum Islam, mazhab fiqh, serta pertimbangan sosial dan budaya lokal. Meskipun tidak ada aturan tegas mengenai usia minimal dalam hukum Islam, banyak negara menetapkan batas usia untuk melindungi individu dari pernikahan dini yang seringkali dikaitkan dengan masalah kesehatan, psikologis, dan kestabilan rumah tangga. Penelitian ini menggunakan metode kualitatif dengan pendekatan komparatif, menelaah berbagai Undang-Undang dan aturan perkawinan di ketiga negara tersebut, serta teori Maqasid al-Shari'ah, yang menekankan perlindungan terhadap keturunan dan kesejahteraan keluarga. Temuan penelitian menunjukkan bahwa Indonesia telah menaikkan usia minimal perkawinan menjadi 19 tahun untuk pria dan wanita, Tunisia menerapkan usia 18 tahun untuk keduanya, sementara di Turki, usia minimal adalah 17 tahun untuk perempuan dan 18 tahun untuk laki-laki. Hasil utama diskusi menunjukkan bahwa perbedaan ini dipengaruhi oleh perbedaan mazhab fiqh dan kebutuhan nasional, seperti pencegahan perceraian dan perlindungan hak-hak anak. Kajian ini menyimpulkan bahwa penetapan usia minimal dalam perkawinan di tiga negara tersebut merupakan bagian dari upaya menjaga keseimbangan antara hukum agama dan realitas sosial. Kata Kunci: Batas Usia Minimal Perkawinan, Negara Muslim, Hukum Perkawinan Islam